Perancangan Media Mobile Learning Berbasis Web MobileMata Pelajaran Komputer dan Jaringan Dasar (Studi Kasus Kelas X TKJ SMK Negeri 2 Padang) - Indra Wijaya; Latifah Annisa (Jurnal KomtekInfo, 2018)
Based on the research conducted at the Vocational High School (SMKN 2Padang) in Class X of Computer and Network Engineering in the odd semester, the average value of the validity test of the 3 validators was obtained for mobile web-based mobile learning media by 91.04%, so that the validity level can be interpreted very valid is used, and the average practicality assessment of mobile web-based mobile learning media is 87.67%, so the practical level can be interpreted very practically in use, and the average assessment of effectiveness test for mobile web-based mobile learning media is 88 , 57%, so that the level of effectiveness can be interpreted to be very effective to use. So, it can be concluded that the Mobile Web Based Mobile Learning Media for Computer and Basic Network subjects in class X Computer and Network Engineering of SMK Negeri 2 Padang is worthy of being used for the learning process.